Pengaruh Volume Lalu Lintas dan Faktor Meteorologi terhadap Konsentrasi Karbon Monoksida (CO) di Udara Jalan Bypass Mojokerto - Tuhu Agung Rachmanto; Slamet Wahyu Hidayat (Prosiding ESEC, 2022)
The Mojokerto Bypass Road is an arterial road that connects the surrounding cities. The road is also passed by as access to the exit of the Mojokerto – Surabaya toll road which is busy against the accumulation of motorized vehicles. This can lead to air pollution, one of which is the emission of carbon monoxide (CO) gas. The pollution causes negative effects for the community around Jalan Bypass Mojokerto in the form of shortness of breath and headaches. This study aims to determine how much the content and influence of traffic volume and meteorological factors on air pollution of Carbon Monoxide (CO) on Jalan Bypass Mojokerto There are 4 measurement points and carried out for 4 days. Analysis of the data used to determine the effect of traffic volume and meteorological factors on carbon monoxide concentrations using Simple Linear Regression with the help of Minitab software version 19. The results of the study showed that the highest concentration of carbon monoxide occurred on Thursday with a value of 9619.63 g/m³. Other results also show that the effect of traffic volume on the concentration of carbon monoxide is the greatest compared to meteorological factors, namely with a value of 11.4% and is directly proportional. This can be suppressed by reducing the use of motorized vehicles and periodic testing of motorized vehicles so that they are safe so that they are in accordance with what is determined by the regulations as well as planting trees so that carbon monoxide is easily degraded.